2020
DOI: 10.1080/14737167.2020.1709965
|View full text |Cite
|
Sign up to set email alerts
|

How cost-effective are new cancer drugs in the U.S.?

Abstract: Introduction: More than 8 times as many new cancer drugs were approved during 2005-2015 as were approved during 1975-1985 (66 vs. 8). The average annual 2010-2014 growth rate of U.S. cancer drug expenditure was 7.6%. This has contributed to a lively debate about the value and cost-effectiveness of new cancer drugs. Areas covered: We assess the average cost-effectiveness in the U.S. in 2014 of new cancer drugs approved by the FDA during 2000-2014, by performing an original econometric investigation (rather than… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 26 publications
1
17
0
1
Order By: Relevance
“…A number of studies of different countries found that the quantity of new treatment approvals was significantly associated with large reductions in premature mortality, and further, that these survival gains were highly cost-effective [28][29][30][31][32][33] . A recent study found similar results for drug approvals in the USA from 2000 to 2014 34 . Given the pace of innovation in cancer treatments in recent years noted above, an update to these studies is timely.…”
Section: Introductionsupporting
confidence: 53%
See 3 more Smart Citations
“…A number of studies of different countries found that the quantity of new treatment approvals was significantly associated with large reductions in premature mortality, and further, that these survival gains were highly cost-effective [28][29][30][31][32][33] . A recent study found similar results for drug approvals in the USA from 2000 to 2014 34 . Given the pace of innovation in cancer treatments in recent years noted above, an update to these studies is timely.…”
Section: Introductionsupporting
confidence: 53%
“…quality of follow-up care), but data on these measures are not available. Even if the quality of care has increased on average, our estimates would not be affected if those changes are not associated with the increase in drug approvals across multiple tumor types 34 . Fifth, unlike cancer mortality rates, incidence rates may suffer from lead-time bias and overdiagnosis, which could give upward bias to the magnitude of the estimates from our main analysis.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…The cost-effectiveness analysis of frequently prescribed drugs is becoming of great value for oncologists and decision-makers, especially for the new and upcoming drugs [19,20]. Thus, cost-effectiveness analyses must consider costs of adverse events management, traveling, and productivity losses, besides the acquisition costs.…”
Section: Discussionmentioning
confidence: 99%